Biotreatment of raisin and winery wastewaters and simultaneous biodiesel production using a Leptolyngbya-based microbial consortium. (1st April 2017) - Tsolcha, Olga N.; Tekerlekopoulou, Athanasia G.; Akratos, Christos S.; Aggelis, George; Genitsaris, Savvas; Moustaka-Gouni, Maria; Vayenas, Dimitrios V.
Abstract: Combining wastewater treatment with biodiesel production can greatly reduce the cost of environmentally friendly technologies. In this work wastewaters of high environmental importance originating from raisin and wine industries were employed as substrates for a mixed cyanobacterial/algal cultivation system dominated by the filamentous cyanobacterium Leptolyngbya sp. The mixotrophic microalga Ochromonas contributed to less than 5% of the total photosynthetic population and grazed on broken Leptolyngbya trichomes. Satisfactory lipid yields and removal of nutrients and chemical oxygen demand (COD) were observed when raisin or winery wastewaters were used separately as substrates. However, exceptional removal rates were recorded in blends of the above-mentioned wastewaters (i.e., 92.8%, 78.1% and 99% for COD, total nitrogen and phosphate, respectively), while the biomass produced contained around 13% lipids (w/w) on a dry weight basis. The ratio of saturated/mono-unsaturated fatty acids in this lipid reached 85%, making this system suitable for biodiesel production. The proposed system can effectively approach a technology that integrates wastewater treatment with simultaneous biodiesel production. Highlights: Treatment of raisin and winery wastewater using microalgae was investigated. Leptolyngbya sp. and wastewater-borne microbes were studied for nutrient removal. High COD removal rates (up to 93%) coupled with lipid production was achieved. Fatty acids derived from microbial lipids biomass led to high quality biodiesel.